Rapid And Sensitive Detection Of Lawsonia Intracellularis In Pigs By Real-Time Loop-Mediated Isothermal Amplification - Byung-Yong PARK (Sciendo, 2015)
A simple and rapid real-time loop-mediated isothermal amplification (LAMP) assay designed to detect Lawsonia (L.) intracellularis, an important bacteria causing proliferative enteropathy in pigs. A set of four primers targeting the ubiquinone/menaquinone biosynthesis methylase (ubiE) gene was designed for the LAMP reaction. Additionally, serial 10-fold dilutions of cultured L. intracellularis and spiked feces were also used for the optimization of real-time LAMP. The lower limit of the linear range of the assay in L. intracellularis was 1.0 × 100L. intracellularis. Real-time LAMP was 10 and 100 times more sensitive than real-time PCR and conventional PCR detection methods, respectively. Based on testing of 213 porcine fecal samples using real-time LAMP, realtime PCR and PCR, the agreement quotients of real-time LAMP with conventional PCR and with real-time PCR were 0.77 and 0.95, respectively. This study demonstrated that real-time LAMP was a powerful tool for the rapid and sensitive detection of L. intracellularis in porcine fecal samples.